Concept and Implementation of Aqd Tabarru' in the Management of ZIS Funds at BAZNAS Kapuas - Danu Pamungkas; Tri Hidayati (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
This study addressed the lack of specific research on the implementation of the tabarru’ contract in the management of ZIS (zakat, infak, and sadaqah) funds, particularly within zakat management institutions such as the National Zakat Agency (BAZNAS) of Kapuas Regency. The Aqd tabarru’, which was grounded in the principles of mutual assistance and non-commercial orientation, held significant potential as an effective Sharia-based framework for managing Islamic social funds. The objective of this research was to explore the concept and practical application of the Aqd tabarru’ at BAZNAS Kapuas, shifting the discussion from its practice in Islamic insurance to its relevance in zakat institutions. This study employs a qualitative descriptive method with a field research design, utilizing interviews, observations, and direct documentation at BAZNAS Kapuas. The findings reveal that the Aqd tabarru’ is implemented in the form of hibah (grant), whereby funds are distributed freely to beneficiaries (mustahik) through transparent and verified social programs. Although the main challenges lie in public zakat literacy and the accuracy of fund distribution, BAZNAS Kapuas addresses these issues through continuous education and the implementation of a Sharia-compliant verification system. This research affirms that the application of the tabarru’ contract in ZIS fund management is not only feasible but also relevant and effective in promoting Sharia-based social justice.